2022
DOI: 10.3389/fpsyg.2022.856697
|View full text |Cite
|
Sign up to set email alerts
|

EEG Microstates in Altered States of Consciousness

Abstract: Conscious experiences unify distinct phenomenological experiences that seem to be continuously evolving. Yet, empirical evidence shows that conscious mental activity is discontinuous and can be parsed into a series of states of thoughts that manifest as discrete spatiotemporal patterns of global neuronal activity lasting for fractions of seconds. EEG measures the brain’s electrical activity with high temporal resolution on the scale of milliseconds and, therefore, might be used to investigate the fast spatiote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
(67 reference statements)
2
10
0
Order By: Relevance
“…The results were similar to our results, which showed that the lower the level of consciousness, the longer the mean duration of the microstate 24 . Lucie Bréchet et al also found that the mean duration of all microstates in the sensor level was longer under sleep and deep anesthesia 25 . The above studies further confirm that longer mean durations of microstates may represent lower brain dynamics in consciousness‐related studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results were similar to our results, which showed that the lower the level of consciousness, the longer the mean duration of the microstate 24 . Lucie Bréchet et al also found that the mean duration of all microstates in the sensor level was longer under sleep and deep anesthesia 25 . The above studies further confirm that longer mean durations of microstates may represent lower brain dynamics in consciousness‐related studies.…”
Section: Discussionsupporting
confidence: 91%
“…24 Lucie Bréchet et al also found that the mean duration of all microstates in the sensor level was longer under sleep and deep anesthesia. 25 The above studies further confirm that longer mean durations of microstates may represent lower brain dynamics in consciousness-related studies.…”
Section: Discussionsupporting
confidence: 64%
“…However, there remains a lack of understanding of the neural mechanisms leading to the presence of microstates and their transitions. It remains unclear how microstates actually reflect conscious thoughts, despite new insights on microstates in various states of consciousness (e.g., sleep, anaesthesia, wakefulness) (Bréchet & Michel, 2022) and rough estimations of the brain sources each microstate class originate from (Bréchet et al, 2020;Britz et al, 2010;Custo et al, 2017;Milz et al, 2017;Musso et al, 2010;Pascual-Marqui et al, 2014). The interpretation of microstates' characteristics often relies heavily on estimated brain sources.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…6 Analysis of clusters consistently reveals four configurations, called EEG microstate classes A to D. 7,8 Microstate temporal dynamics are sensitive to neuropsychiatric conditions 9,10 and altered states of consciousness. [11][12][13] Schizophrenia patients and their siblings have a higher prevalence of class C and a lower prevalence of class D. 9 All classes of Lewy body dementia have longer microstate durations in comparison with controls, but the occurrence of each class is lower than that in controls. 14 In the case of prolonged disorders of consciousness (pDoC), there were fewer classes of microstates, 15 and microstate D proved to be the most precise metric for discerning between VS/UWS and MCS.…”
Section: Introductionmentioning
confidence: 99%